Synthesis of 3-amino-2-(2-chlorophenyl)quinazolin-4(3H)-one by Conventional heating and Microwave Irradiation - Luthfi Ahmad Muchlashi (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2021)
This study aims to compare conventional heating with microwave irradiation in order to obtain the optimal method for 3-amino-2-(2-chlorophenyl)quinazolin-4(3H)-one synthesis. For the compound to be completely synthesised, one needs to carry out much heating for a long period of time. 10 hours are required for the reaction using conventional heating; yet it takes only 5 minutes using microwave with 800 watts of power. It was found in this study that there was an improvement in percent yields of 3-amino-2-(2-chlorophenyl)quinazolin-4(3H)-one, 87 % using microwave irradiation compared to 79 % using reflux. Therefore, microwave-assisted method is a quicker, higher yielding method for 3-amino-2-(2-chlorophenyl)quinazolin-4(3H)-one synthesis.